Patient education materials to implement choosing wisely recommendations for internal medicine at the emergency department. Issue 1 (4th February 2021) - Laan, Bart J; Huiszoon, Willemijn B; Holleman, Frits; Boermeester, Marja A; Kaasjager, Karin A H; Geerlings, Suzanne E
Abstract : Background: Choosing Wisely aims to reduce low-value care to improve quality and lower costs. In the Netherlands, this campaign offers three recommendations for internal medicine applicable in emergency departments (EDs): (1) do not place an indwelling urinary catheter in non-critically ill patients who can void; (2) do not order plain abdominal radiographs in patients with acute abdominal pain; and (3) discuss whether treatment limitations are needed. This quality improvement project aims to increase the implementation of the recommendations by patient information leaflets. Methods: In a prospective before–after study, we collected data every other week during baseline and intervention periods (both 7 months) in two university medical centres. The primary outcomes were the adherence rates to the recommendations. Results: 805 patients visited the EDs for internal medicine, of whom 391 (48.6%) were hospitalised. Only 153 (19%) patients received the information leaflet. We found no change in implementation rates of the recommendations after the introduction of the patient information leaflet. In the baseline period, 28 patients received a urinary catheter, of whom 5 (17.9%) had no appropriate indication, compared with 4 (25.0%) of 16 patients in the intervention period (p=0.572). Unnecessary abdominal X-ray occurred once in the baseline period and not in the intervention period. Treatment limitations were not reported in 13 (6.5%) of 200 hospitalised patients in the baseline period, and in 17 (8.9%) of 191 patients in the intervention period (p=0.373). Conclusions: Patient information leaflets did not increase the implementation of Choosing Wisely recommendations, which can be due to a high baseline rate and a poor dissemination of leaflets. Our ED seems not to be a practicable setting for dissemination of leaflets, since staff engagement was not possible due to high workload and shortage of qualified nursing staff in the Netherlands.